A molecular phylogeny of the “Madascincus polleni species complex”, with description of a new species of scincid lizard from the coastal dune area of northern Madagascar - Miralles, Aurélien; Köhler, Jörn; Glaw, Frank; Vences, Miguel (Zootaxa, 2011)
The present paper constitutes a study on a taxonomically confusing group of closely related species belonging to the Malagasy skink genus Madascincus, currently encompassing the nominal species M. polleni, M. intermedius and M. stumpffi. Based on combined analyses of mitochondrial and nuclear DNA sequences (ND1 and RAG2 genes, respectively), and morphological examination, we provide evidence for the existence of at least four distinct evolutionary lineages within this complex: Madascincus stumpffi; Madascincus arenicola sp. nov. from northern Madagascar; and two cryptic species morphologically similar to the name-bearing types of M. polleni and M. intermedius. The two latter species, although genetically distinct, appear to be morphologically indistinguishable and their taxonomic status cannot be resolved until a better sampling will be available.